A STUDY OF THE SPECTRUM OF PRESENTING SYMPTOMS, DIAGNOSTIC INVESTIGATIONS, TREATMENT AND OUTCOME OF SEVERE MALARIA IN THE ADMITTED CHILDREN OF KUWAIT TEACHING HOSPITAL, PESHAWAR, PAKISTAN - Ullah, Saffi; Ali, Saima; Salahuddin, Abid; Qureshi, Muhammad Salman H (Journal of Postgraduate Medical Institute, 2016)
Objectives: To document the spectrum of presenting symptoms, diagnostic investigations, treatment and outcome of severe malaria in the hospitalized children of Kuwait teaching hospital. Methodology: This was a descriptive study using patient case records of children admitted from 1st January till 31st December 2013. All children with malaria requiring admission and treatment with parenteral anti-malarial were categorized as severe malaria and included in the study. Data was analyzed using Microsoft office Excel 2007. Results: 32 cases fulfilled the inclusion criteria. Fever was the commenest presenting symptoms present in 100% of cases (n=32). Fifty percent chil-dren (n=16) had pallor, 12.5 %( n= 4) cough, 9.3 %( n=3) had dysuria and 6.25 %( n=2) had fits recorded as additional presenting symptoms. 71.8% (n=23) had parasitological confirmation test before commencement of treatment .100% of this parasitological confirmation was done by peripher -al blood smear/microscopy test. Out of the 23 who had microscopy done 60.86%(n=14) had negative result and 39.13%(n=9 )were positive for plasmo-dium of which,88.88%(n=8)were vivax and 11.11%(n=1) was falciparum.93.75 %(n=30) of the parenteral anti-malarial used was intravenous quinine. All ex-cept one child 96.8 %( n=31) recovered with the anti-malarial treatment used. Conclusions: Fever and pallor are the two most common presenting symp -toms of hospitalized children with severe malaria. Microscopy remained the most common investigation for the diagnosis of malaria. Quinine is the most frequently used drug for severe malaria. The study highlighted the need to further improve the case management of severe malaria in children.